2020
DOI: 10.1097/ico.0000000000002463
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Epi-On Versus Standard Epi-Off Corneal Collagen Cross-Linking for Progressive Keratoconus in Pediatric Patients: Five Years of Follow-Up

Abstract: Purpose: The purpose of this study was to evaluate and compare the 5-year efficacy and safety of accelerated transepithelial (A-epi-on) corneal collagen cross-linking (CXL) with standard CXL (epi-off) in children with progressive keratoconus (KC). Methods: This prospective cohort study included 78 eyes of patients aged 18 years old or younger with progressive KC who underwent CXL at the Oftalmosalud Institute of Eyes, Lima, Peru. A-epi-on CXL was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 21 publications
2
28
2
Order By: Relevance
“…Buzzonetti, in a study of the efficacy of TCXL in pediatric KC, with an average age group of 14.4 years (± 3.7 years), with an 18-month follow-up, observed worsening of K max, concluding that this method does not effectively reduce the progression of KC compared to SCXL [ 79 ]. In a comparative study, Henriquez et al showed that although both procedures halted the progression of KC at 5 years of follow-up, SCXL was able to halt it at a significantly higher level and with a higher flattening effect than TCXL [ 84 ]. Compared with SCXL, I-CXL could stop KC progression as much as 12 months, as disease progression was found in 50% of cases at a 24-month follow-up [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Buzzonetti, in a study of the efficacy of TCXL in pediatric KC, with an average age group of 14.4 years (± 3.7 years), with an 18-month follow-up, observed worsening of K max, concluding that this method does not effectively reduce the progression of KC compared to SCXL [ 79 ]. In a comparative study, Henriquez et al showed that although both procedures halted the progression of KC at 5 years of follow-up, SCXL was able to halt it at a significantly higher level and with a higher flattening effect than TCXL [ 84 ]. Compared with SCXL, I-CXL could stop KC progression as much as 12 months, as disease progression was found in 50% of cases at a 24-month follow-up [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“… 2019 ; Henriquez et al. 2020 ). Several studies show outcomes after epi‐on treatment similar to the standard CXL procedures (Magli et al.…”
Section: Discussionmentioning
confidence: 99%
“…Keeping the epithelium intact during CXL could reduce pain and complications, such as delayed reepithelialization, haze formation and microbial keratitis. It is, therefore, that many studies have focused on delivering RF to the corneal stroma without the removal of the epithelium, known as 'epi-on' CXL, by addition of penetration enhancers, alteration of the riboflavin formulation or by the use of iontophoresis(Beckman et al 2019;Henriquez et al 2020). Several studies show outcomes after epi-on treatment similar to the standard CXL procedures(Magli et al 2013;Stojanovic, Zhou & Utheim 2014;Nawaz et al 2015;Rossi et al 2015;Stulting et al 2018).…”
mentioning
confidence: 99%
“…As such, it is more accepted and preferred all over the world as being a safer and more effective method in the long term. 93 , 94 …”
Section: Advances In Treatmentmentioning
confidence: 99%
“…As such, it is more accepted and preferred all over the world as being a safer and more effective method in the long term. 93,94 New keratoplasty procedures The last two decades have seen a paradigm shift in keratoplasty moving from the insertion of fullthickness grafts to lamellar grafts. A lamellar approach not only decreases the likelihood of immune rejection but also offers less-induced astigmatism and better visual outcomes particularly in the case of endothelial transplants.…”
Section: Advances In Treatmentmentioning
confidence: 99%